2014
DOI: 10.1007/978-94-017-8881-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Perforin and Human Diseases

Abstract: Natural killer (NK) cells and cytotoxic T lymphocytes (CTL) use a highly toxic pore-forming protein perforin (PFN) to destroy cells infected with intracellular pathogens and cells with pre-cancerous transformations. However, mutations of PFN and defects in its expression can cause an abnormal function of the immune system and difficulties in elimination of altered cells. As discussed in this chapter, deficiency of PFN due to the mutations of its gene, PFN1, can be associated with malignancies and severe immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…A control group of Prf −/− mice was infected with VSV alone. Perforin is the primary cytotoxic effector protein in CD8 + T cells . We found that Prf −/− mice infected with chronic LCMV and then superinfected with VSV exhibit a much more impaired B‐cell response than do Prf −/− mice infected with VSV alone (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…A control group of Prf −/− mice was infected with VSV alone. Perforin is the primary cytotoxic effector protein in CD8 + T cells . We found that Prf −/− mice infected with chronic LCMV and then superinfected with VSV exhibit a much more impaired B‐cell response than do Prf −/− mice infected with VSV alone (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…However, the related pore-forming proteins, Perforin-1 and complement C9, are well studied and understood. Recessive mutations in PFN1 (encoding Perforin-1) are associated with poor control of viral infections and lead to the immune disorder familial hemophagocytic lymphohistiocytosis (FHL) (26). Importantly, and relevant to these variants in MPEG1, heterozygous changes in Prf1 in mice and PRF1 in humans are associated with impaired NK function and contribute to the development of hemophagocytic lymphohistiocytosis (HLH) (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…58 Indeed, mutations within PRF1 gene and defects in its expression can cause an abnormal function of the immune system. 59 …”
Section: Discussionmentioning
confidence: 99%